Flash-induced ultrafast recrystallization of perovskite for flexible light-emitting diodes. (July 2019) - Jung, Dong Hun; Park, Jung Hwan; Lee, Han Eol; Byun, Jinwoo; Im, Tae Hong; Lee, Gil Yong; Seok, Jae Young; Yun, Taeyeong; Lee, Keon Jae; Kim, Sang Ouk
Abstract: We report ultrafast recrystallization of perovskite (methylammonium lead tribromide, MAPbBr3 ) by flash light annealing (FLA) for light-emitting diode (LED) application. Intense near-infrared (NIR) peak spectrum (830 and 900 nm) of flash light could rapidly heat MAPbBr3 based LED structures over ∼320 °C without radiative damage. Cuboidal morphology of the perovskite active layer was evolved into the dense recrystallized structure with a noticeably small grain size (∼38 nm) by FLA, which significantly promoted the radiative recombination. Surface roughness (root mean square (RMS)) of the perovskite layer was decreased by 62% (from 8.47 to 3.22 nm) via FLA, while inhibiting the leakage current that limit current efficiency (CE) of perovskite LED (PeLED). Three dimensional temperature simulation was investigated for the mechanism of flash-induced MAPbBr3 recrystallization. Finally, FLA was successfully exploited for the flexible PeLEDs on polyethylene naphthalate substrates, which exhibited 252% larger CE compared to thermally annealed counterpart. Graphical abstract: Image 1 Highlights: Ultrafast recrystallization of perovskite is demonstrated by flash light annealing (FLA). Cuboidal MAPbBr3 was transformed into dense film with small grain size down to ~38 nm and smooth surface by FLA. Current efficiency of MAPbBr3 light emitting diode was enhanced by 263% via FLA compared with thermally annealed counterpart.